The World after COVID-19 and its impact on Global Economy - Mukesh Kumar Mishra (ZBW – Leibniz Information Centre for Economics, 2020)
Urgent and bold policy measures are needed, not only to contain the pandemic and save lives, but also to protect the most vulnerable in our societies from economic ruin and to sustain economic growth and financial stability. We are facing a global health crisis unlike any in the 100-year history, one that is killing people, spreading human suffering, and upending people's lives. But this is much more than a health crisis. It is a human, economic and social crisis. The coronavirus disease (COVID-19), which has been characterized as a pandemic by the World Health Organization (WHO), is attacking societies at their core. The global economy could shrink by up to 1 per cent in 2020 due to the coronavirus pandemic, a reversal from the previous forecast of 2.5 per cent growth, the UN has said, warning that it may contract even further if restrictions on the economic activities are extended without adequate fiscal responses. The COVOD-19 pandemic will cause a dramatic drop in FDI flows. MNEs, local business and investment have been severely affected with far reaching social and economic repercussions. The coronavirus crisis is first and foremost a public health threat, but it is also, and increasingly, an economic threat. The so-called “Covid-19” shock will trigger a recession in some countries and a deceleration of global annual growth to below 2.5 per cent – often taken as the recessionary threshold for the world economy . The world is being flooded with perhaps unfamiliar words and phrases in coverage of COVID-19, the newly discovered coronavirus — starting with the very word "coronavirus." The new coronavirus, which first emerged in the Chinese city of Wuhan last December, has infected more than 210,000 people in at least 171 countries and territories globally, according to the World Health Organization. The on-going spread of the new coronavirus has become one of the biggest threats to the global economy and financial markets.
Keywords: F62; F69; 330; Global Economy; International Organization